2017
DOI: 10.1177/0022002717701818
|View full text |Cite
|
Sign up to set email alerts
|

Gender-empathic Constructions, Empathy, and Support for Compromise in Intractable Conflict

Abstract: The goal of the present study was to investigate how empathy and gender-empathic constructions affect the levels of support for political compromise in an intractable conflict. Gender-empathic constructions relate to perceptions that individuals hold about self or others as having feminine-empathic gender traits. We hypothesized that empathy will be positively associated with support for compromise, but that perceiving one’s own group as feminine empathic will be negatively associated with such attitudes, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 98 publications
(154 reference statements)
1
8
0
Order By: Relevance
“…The correlation between the 12% of the participants who indicated they trust the Palestinian leader and the 12% who perceived the news item as reliable suggests that prior real-world knowledge, rather than the textual design, could have affected the participants’ judgments and pushed them to react to Abbas’ decision with a highly skeptical attitude. In addition, the data conformed with previous studies (David and Maoz, 2015; David et al, 2018) and indicated that Jewish-Israelis express a medium level of support for political compromise ( M = 3.23, SD = 1.51), with 38% of the participants supporting a possible peace initiative (ratings of 4, 5 or 6 on the 1–6 scale). In contrast to the issue of trusting the proposing leader, the reliability of the news item had no significant influence on support for political compromise.…”
Section: Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…The correlation between the 12% of the participants who indicated they trust the Palestinian leader and the 12% who perceived the news item as reliable suggests that prior real-world knowledge, rather than the textual design, could have affected the participants’ judgments and pushed them to react to Abbas’ decision with a highly skeptical attitude. In addition, the data conformed with previous studies (David and Maoz, 2015; David et al, 2018) and indicated that Jewish-Israelis express a medium level of support for political compromise ( M = 3.23, SD = 1.51), with 38% of the participants supporting a possible peace initiative (ratings of 4, 5 or 6 on the 1–6 scale). In contrast to the issue of trusting the proposing leader, the reliability of the news item had no significant influence on support for political compromise.…”
Section: Methodssupporting
confidence: 87%
“…Support for political compromise was based on three questions (adapted from David and Maoz, 2015; David et al, 2018; Shamir and Shikaki, 2010) that were rated on a 6-point scale ranging from strongly disagree (1) to strongly agree (6). Responses to the three items were averaged for each respondent to create one scale according to which a high score means high support for political compromise.…”
Section: Methodsmentioning
confidence: 99%
“…However, as previous research has shown, in addition to its clearly positive connotations and effects (David et al, 2018; Maoz, 2009), the association of women, femininity, and peace can elicit negative responses and stereotypes. Critical work discusses feminization as part of a derogatory construction of ethnic, national, or religious minority groups, which serves both to legitimize social and moral exclusion and to allow for physical and structural violence against these minorities, violating their human rights (David et al, 2016; Kaufman & Williams, 2013; Suleiman, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Research literature on gender, intergroup conflicts, and peace processes points to the effect of gender and gender-related expectations and perceptions on support for militant actions or for compromise in conflict (David et al, 2018; Maoz, 2009; Tessler & Warriner, 1997). Previous studies have demonstrated that encountering female outgroup members (Maoz, 2009), as well as perceiving the outgroup as possessing feminine traits, reduces threat perceptions and decreases support for violating human rights in conflict (David et al, 2016) while increasing the readiness for conflict resolution based on compromise (David & Maoz, 2015; Maoz, 2009).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, other studies-also conducted in the context of the Israeli-Palestinian conflict-indicate apparently paradoxical effects, whereby exposure to narratives of suffering of the other side in conflict elicits hostile responses, distrust, competitive victimhood, a sense of threat and even an escalation of animosity (Cohrs, McNeill & Vollhardt, 2015;Maoz, 2008;Mor et al, 2016;Nagar & Maoz, 2017a, 2017bRosenberg & Maoz, 2012). Moreover, polling data show an inverse association between perceiving one's own group as compassionate and feeling empathy toward the outgroup in conflict (David, Rosler, & Maoz, 2017).…”
Section: Encountering Narratives Of the Suffering Of Others In Conflimentioning
confidence: 96%